2018
DOI: 10.18410/jebmh/2018/141
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Effects of Smoking on Lipid Profile Among Healthy Smokers and Non-Smokers

Abstract: BACKGROUND Coronary artery disease forms a major non-communicable disease in both developed and developing countries. In western countries, older age groups are affected whereas in our country India, it is common among younger age group. Many risk factors have been evaluated. Cigarette smoking contributes for major risk factor for coronary artery disease, atherosclerosis and peripheral vascular disorders. Mechanism of causing coronary artery disease is multifactorial, it has major adverse effects on lipid prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The dose-response analysis showed that the chance of abnormal level of LDL and HDL in participants who smoked more than 20 pack-years, respectively, is 2.64 and 2.24 times more than participants who smoked less than 10 pack-years. Previous research has already concluded that smoking is linked to unfavorable changes in lipid profile, including elevated TC, LDL, and TG, as well as decreased HDL levels, all of which are indicators of cardiovascular risk (Girish & Harish, 2018). Hence, based on our findings, it can be concluded that smoking has a significant negative impact on HDL-cholesterol levels, even after accounting for other factors.…”
Section: Association Between Smoking and Lipid Profilesupporting
confidence: 65%
See 2 more Smart Citations
“…The dose-response analysis showed that the chance of abnormal level of LDL and HDL in participants who smoked more than 20 pack-years, respectively, is 2.64 and 2.24 times more than participants who smoked less than 10 pack-years. Previous research has already concluded that smoking is linked to unfavorable changes in lipid profile, including elevated TC, LDL, and TG, as well as decreased HDL levels, all of which are indicators of cardiovascular risk (Girish & Harish, 2018). Hence, based on our findings, it can be concluded that smoking has a significant negative impact on HDL-cholesterol levels, even after accounting for other factors.…”
Section: Association Between Smoking and Lipid Profilesupporting
confidence: 65%
“…Previous research has already concluded that smoking is linked to unfavorable changes in lipid profile, including elevated TC, LDL, and TG, as well as decreased HDL levels, all of which are indicators of cardiovascular risk ( Girish & Harish, 2018 ). Hence, based on our findings, it can be concluded that smoking has a significant negative impact on HDL-cholesterol levels, even after accounting for other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported an increase in the cholesterol levels in the smoker group when compared to the non-smoker group (Alharbi, 2011;Devaranavadgi et al, 2012;Gopdianto, Wuling & Ticoalu, 2013;Hassan et al, 2013;Adelina, Handayani & Kurniawan, 2016;Attard et al, 2017;Girish & Harish, 2018). However, the studies on differences in cholesterol levels in tobacco smokers and electronic-cigarette smokers are limited.…”
Section: Resultsmentioning
confidence: 99%
“…Nicotine, a poison contained in smoke tobacco, is known to have an effect on the secretion of catecholamines and cortisol which can then change the metabolism of carbohydrates and fats. Changes in lipid metabolism can initiates dyslipidemia (Girish & Harish, 2018). Therefore, this study aimed to compare the cholesterol levels in tobacco smokers and electronic smokers.…”
Section: Introductionmentioning
confidence: 99%